Recent developments in immunisation practice. Issue 3 (March 2017) - Marlow, Robin; Metz, Jane; Chesshyre, Emily; Sarra, Aikaterini; Finn, Adam
Abstract: Over the last 5 years the UK has led the world in the introduction of new vaccines with substantial changes in the childhood vaccination schedules. These have been both in response and in anticipation of changes in the epidemiology of illness and demonstrate the importance of public health screening and the notification of infectious diseases. This review article briefly outlines the rationale and history behind these most recent developments and highlights potential changes on the horizon.